Decentralization of Health Service at Darussalam Public Health Center Medan - Fildza Hafart; Muhammad Husni Thamrin Nasution (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2022)
The problem with health decentralization in Indonesia is that health decentralization is still half-hearted. The policy direction in the health sector initially rested on efforts to treat disease and restore health. And next, policy direction has also shifted towards implementing comprehensive health efforts with an emphasis on disease prevention and health promotion. The shift also occurred in the focus of policy direction in the health sector, which initially focused on individual health, which then shifted to public health. This study aims to determine how the decentralization of health service delivery at the Darussalam Public Health Center, Medan City. type of research in this study is a qualitative research with a descriptive approach in the form of written or spoken words from people and observable behavior. data collected is in the form of words, pictures, and not numbers. All the data collected may be the key to what has been researched. The results showed that the planning, budgeting, and management processes were still relatively slow because they had to get approval from the Medan City Health Office. The Darussalam Health Center can only submit this deficiency to the Medan City Health Office. because the one who has the authority to make repairs is the Medan City Health Office.There are still obstacles in the referral process,because there are several administrations that must be completed and the procedures must also comply with the specified standards.